Предмет: Алгебра,
автор: tessaletyago
4(3х+4)(х+2)(1-2х)-3(4х+3)(2-х)(1+2х)=-43(2х+3)(х+2)-12
РЕШИТЕ ПЛЕС ДЛЯ ПРОВЕРКИ НАДО!!!СРОЧНО!
Ответы
Автор ответа:
0
4*(3*x+4)*(x+2)*(1-2*x)-3*(4*x+3)*(2-x)*(1+2*x) = -43*(2*x+3)*(x+2)-12
32 - 68*x^2 - 24*x - 24*x^3 - (3*(4*x + 3))*(2 - x)*(1 + 2*x) = -43*(2*x+3)*(x+2)-12
32 - 68*x^2 - 24*x - 24*x^3 - 18 - 51*x - 18*x^2 + 24*x^3 = -43*(2*x+3)*(x+2)-12
32 - 68*x^2 - 24*x - 24*x^3 - 18 - 51*x - 18*x^2 + 24*x^3 = - 258 - 301*x - 86*x^2 - 12
284 + 226*x = 0
226x=-284
x= - 284/226 | :2
x= - 142/113
32 - 68*x^2 - 24*x - 24*x^3 - (3*(4*x + 3))*(2 - x)*(1 + 2*x) = -43*(2*x+3)*(x+2)-12
32 - 68*x^2 - 24*x - 24*x^3 - 18 - 51*x - 18*x^2 + 24*x^3 = -43*(2*x+3)*(x+2)-12
32 - 68*x^2 - 24*x - 24*x^3 - 18 - 51*x - 18*x^2 + 24*x^3 = - 258 - 301*x - 86*x^2 - 12
284 + 226*x = 0
226x=-284
x= - 284/226 | :2
x= - 142/113
Похожие вопросы
Предмет: Английский язык,
автор: milankaw5
Предмет: Математика,
автор: coometcomet
Предмет: География,
автор: nurseitsatybaev72
Предмет: Литература,
автор: nataliababkina
Предмет: Обществознание,
автор: rfnz15